2000
DOI: 10.1088/0953-8984/12/50/320
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic circular dichroism and optically detected magnetic resonance investigation of Fe2+and Fe3+centres in KTaO3

Abstract: A cubic and an axial Fe 2+ centre, Fe 2+ Ta and Fe 2+ Ta -V O , are found in reduced Fe-doped KTaO 3 crystals in conjunction with their trivalent partners. These four defects are characterized by optically detected magnetic resonance (ODMR) via the magnetic circular dichroism (MCD) of the absorption. The g-values are determined by and interpreted using crystal-field terms. For all centres, the optical absorption bands are identified by the tagged-MCD method. The main MCD bands of the divalent ions are attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…A controversy exists in the literature concerning the sign of D for the Fe 3+ K -O 2− I center. The sign of D = 4.46 cm −1 has unequivocally been determined experimentally as positive [9,10], and thus represented as such by other authors, see, e.g., [4,6,7,[13][14][15]. However, in a recent paper Zheng et al [16] have claimed that Bykov et al [9] did not determine the sign of D. The authors [16] have compared their negative theoretical values of D with the alleged experimental value D expt = −4.46 cm −1 , just disregarding the bulk of experimental evidence [4,6,7,9,10,[13][14][15].…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…A controversy exists in the literature concerning the sign of D for the Fe 3+ K -O 2− I center. The sign of D = 4.46 cm −1 has unequivocally been determined experimentally as positive [9,10], and thus represented as such by other authors, see, e.g., [4,6,7,[13][14][15]. However, in a recent paper Zheng et al [16] have claimed that Bykov et al [9] did not determine the sign of D. The authors [16] have compared their negative theoretical values of D with the alleged experimental value D expt = −4.46 cm −1 , just disregarding the bulk of experimental evidence [4,6,7,9,10,[13][14][15].…”
Section: Introductionmentioning
confidence: 65%
“…Bykov et al [9] have determined that D does not depend on temperature for the former center, whereas it reduces linearly with temperature for the latter center. The site assignments were confirmed by the optically detected magnetic resonance and the magnetic circular dichroism [6,11]. Structural models proposed by Laguta et al [7] for the two axial Fe 3+ centers have been confirmed by the authors' ENDOR studies and additionally by the electric-field-induced orientation studies by Sochava et al [12] for the Fe 3+ K -O 2− I center.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations